ANALYSIS OF FORECASTING THE NUMBER OF STUDENTS USING VECTOR AUTOREGRESSION COMPUTER BASED - Djunaidy Santoso (Institut Bisnis dan Informatika Kwik Kian Gie, 2016)
Education has become an important factor in a person's life. Therefore, many people who race - the race to get the best education. The course, has become one of the places entrusted by parents in providing additional lessons to their children. Forecasts for the large number of students can be used as a benchmark in determining the success or failure of an educational institution. In addition, can also be used as an assessment of the services rendered, as more and more students are obtained, meaning the greater the trust that is given to perusahaan.Pengumpulan data is done by the secondary, which uses data drawn from the data in the previous period. The data used is the actual data obtained from Valto Education Centre.Data that has been collected will then be processed using Microsoft Excel 2003. The method used was Vector Autoregression[1]. Data processing will generate value for the first forecast future periods. Keywords: Vector Autoregression, Time Series, autocorrelation, Forecasting